Local Wisdom in the Oral Tradition of the Seven-Month Pregnancy Ritual: An Ecolinguistic Study - Nursaima Harahap; Armita Novriana Rambe; Sofa Priyandayani Nasution; Feby Feby; Luki Aswar (MASI Mandiri Edukasi, 2025)
This study explores the values of local wisdom within the Mandailing community's seven-monthly oral traditions, emphasising its significance in understanding the intricate relationship between culture, language, and the environment. The primary objective is to describe these values through an ecolinguistic perspective, supported by an ethnographic study of communication. The research employs listening and note-taking methods, ethnographic conversation, and recording techniques for data collection. The analysis utilises extra-lingual matching and contextual analysis to identify and interpret the embedded wisdom. Our findings reveal that local wisdom manifests in tangible forms, such as rice wrapped in leaves, gala shrimp, carp, and eggs, and intangible forms, exemplified by words of advice and admonition. These manifestations collectively embody noble values deeply rooted in the Mandailing people's culture. This research contributes to ecolinguistics by highlighting how oral traditions are a repository for cultural values and environmental knowledge.